3D graphics application/game on mobile phone III - Renaldo Lianto. (2010)
In their early days, mobile phones are considered of no more than communication devices. Games are only considered as optional applications for mobile phones, and only feature limited 2D graphics. However, 3D games and applications have become a growing niche in the mobile phone sector. Mobile phones have started to support 3D graphics, and various 3D APIs have been created in order to ease the development process of a 3D application. One of the APIs is M3G (Mobile 3D Graphics).